Formation of nanocrystalline cellulose by using task specific ionic liquids / Nurul Atikah Mohd Iskak - Nurul Atikah , Mohd Iskak (2017)
Nanocrystalline cellulose (NCC) has been classified as a new category of cellulose matter and has been used in various technical extents such as in medicinal and biotechnological areas. The nanocrystalline cellulose is typically constructed by the reaction of condensed and toxic acid on primal cellulose samples at different temperatures to ensure ultrasound breakdown. However, the current method for the formation of nanocrystalline cellulose is neither environmentally friendly nor energy efficient. Therefore, this study made use of ionic liquids, 1-butyl-3-methylimidazolium chloride as an alternative to produce nanocrystalline cellulose. Comprehensive investigations on different parameters, such as ultrasonication time, ultrasonication vibration, temperature, dissolution time and microcrystalline cellulose to ionic liquids ratio were conducted in order to control the specific architecture of nanocrystalline cellulose. This study utilizes 1-butyl-3-methylimidazolium chloride followed by ultrasonication to produce nanocrystalline cellulose with a rod-like structure from microcrystalline cellulose. The crystalline structure was noted as Cellulose I, which is similar to the starting materials. Increasing the vibration amplitude of the ultrasonication increases the yield, crystallinity index, thermal properties and particle size of the NCC. Meanwhile, decreasing the ultrasonication time improved the crystallinity, thermal properties and particle size of the NCC. Increasing the temperature, dissolution time and microcrystalline cellulose to ionic liquids ratio enhance the crystallinity, yield, thermal properties, and also the diameter size of the NCC. Optimized conditions were recorded to be as followings: ultrasonication time (5 minutes), ultrasonication vibration (70%), temperature (100°C), dissolution time (30 minutes) and microcrystalline cellulose to ionic liquids ratio (1:10). In conclusion, 1-butyl-3-methylimidazolium chloride is a suitable alternative to the conventional solvents with the optimized parameters as described above.